Identification and characterization of novel marine oxasqualenoid yucatecone against Naegleria fowleri - Iñigo Arberas-Jiménez; Francisco Cen-Pacheco; Javier Chao-Pellicer; Ines Sifaoui; Aitor Rizo-Liendo; Ezequiel Q. Morales; Antonio H. Daranas; Ana R. Díaz-Marrero; José E. Piñero; José J. Fernández; Jacob Lorenzo-Morales (International Journal for Parasitology: Drugs and Drug Resistance, 2023)
Naegleria fowleri is an opportunistic protozoan, belonging to the free-living amoeba group, that can be found in warm water bodies. It is causative agent the primary amoebic meningoencephalitis, a fulminant disease with a rapid progression that affects the central nervous system. However, no 100% effective treatments are available and those that are currently used involve the appearance of severe side effects, therefore, there is an urgent need to find novel antiamoebic compounds with low toxicity. In this study, the in vitro activity of six oxasqualenoids obtained from the red algae Laurencia viridis was evaluated against two different strains of N. fowleri (ATCC® 30808 and ATCC® 30215) as well as their cytotoxicity against murine macrophages. Yucatecone was the molecule with the highest selectivity index (>2.98 and 5.23 respectively) and it was selected to continue with the cell death type determination assays. Results showed that yucatone induced programmed cell death like responses in treated amoebae causing DNA condensation and cellular membrane damage among others. In this family of oxasqualenoids, it seems that the most significative structural feature to induce activity against N. fowleri is the presence of a ketone at C-18. This punctual oxidation transforms an inactive compound into a lead compound as the yucatecone and 18-ketodehydrotyrsiferol with IC50 values of 16.25 and 12.70 μM, respectively. The assessment of in silico ADME/Tox analysis revealed that the active compounds showed good Human Oral Absorption and demonstrate that are found to be within the limit of approved drug parameter range. Hence, the study highlights promising potential of yucatone to be tested for therapeutic use against primary amoebic meningoencephalitis.